The Sentiments of Students and Teachers on Modular Distance Learning Amid the Health Crisis - Mariel A. De Aquino; Argilyn M. Balingit; Airen D. Bontog; Pamela Jane S. Fortugaliza; Melbert O. Hungo; Leomarich F. Casinillo (Indonesian Journal Of Educational Research and Review, 2023)
Due to the COVID-19 pandemic, schools, particularly in rural areas, employed Modular Distance Learning (MDL) to ensure educational continuity. Modular distance learning is the current learning modality of primary education, where parents serve as parent-teachers to their children. This study seeks to evaluate the experiences of students and teachers of Elementary School, on modular distance learning during the pandemic. This study used the qualitative method of interviewing nine students and six teachers to learn about their MDL experiences. Data process involves combining related concepts and themes to produce a more structured and organized picture of the data. MDL strengthens family bonding, promotes independent learning, and economizes money and time. However, it is an additional workload for working parents; there needs to be more teacher-student interaction, preventing pupils from socializing and gadget distractions. The article revealed that MDL has positive and negative experiences for teachers and students. Therefore, the impact may vary depending on individual circumstances and adaptability. The study suggests that suitable strategies should address any challenges during implementation and evaluation. Furthermore, teachers must undergo training related to MDL to address existing problems in delivering their lessons.